Difratando vivências na África do Sul por meio de uma perspectiva pós-humanista crítica a fim de um movimento investigativo decolonial - Souza, Luzia Aparecida De; Silva, Heloisa Da [UNESP] (UNESP - Universidade Estadual Paulista, Pró-Reitoria de Pesquisa; Programa de Pós-Graduação em Educação Matemática, 2025)
This article aims to analyze and share snapshots of the formative experiences of two researchers in Mathematics Education during their postdoctoral studies in the School of Education at the University of Cape Town, South Africa. Through a diffractive writing approach, drawing from images and experiences in South Africa, we articulate a critical posthumanist perspective on the ways of operating these mathematics educators. Based on field notebooks, focus groups, and interviews (which will not be specifically addressed in this text), this paper connects experiences in a teacher education course, an international project involving basic education schools, students, and communities, as well as in the streets and in working with/in a research group, with the aim of affirming possibilities for a Mathematics Education that challenges the binary organization of a world that demands to be read through an intersectional lens.

Este artigo tem o objetivo de analisar e compartilhar cortes na experiência formativa de duas pesquisadoras em Educação Matemática durante seu pós-doutorado na Faculdade de Educação da Universidade da Cidade do Cabo, África do Sul. Em uma escrita difrativa, a partir de imagens e experiências na África do Sul, articulamos a perspectiva pós-humanista crítica aos modos de operar dessas educadoras matemáticas. A partir de registros em cadernos de campo, grupos focais e entrevistas (que não serão, aqui, especificamente tematizados) este texto articula experiências em um curso de formação de professores; em um projeto internacional que envolveu escolas da educação básica, estudantes e comunidades; nas ruas e no trabalho com/em um grupo de pesquisa com o intuito de afirmar possibilidades para uma Educação Matemática que lute contra a organização binária de um mundo que demanda ser lido em interseccionalidade.
Diffracting Experiences in South Africa Through a Critical Posthumanist Perspective for a Decolonial Investigative Movement
Keywords: Critical posthumanism; Education (mathematics; Diffractive writing and pedagogy; Formative processes; Pós-humanismo crítico; Educação (Matemática; Escrita e pedagogia difrativas; Processos formativos